Analisis Pembiayaan Sektor Pertanian pada BPRS dengan Perspektif Kesejahteraan dan Risiko - Essa, Satrija Prajna; Burhany, Dian Imanina; Syarief, M. Edman (Jurnal Manajemen Bisnis dan Keuangan, 2022)
This study aims to assess the effect of bias regret and overconfidence on cryptocurrency This study aims to examine the effect of two aspects that form the basis for the distribution of financing carried out by BPRS for the agricultural sector, namely farmer welfare and financing risk. This study uses a sample of 163 BPRS incorporated in the report published by the OJK with monthly data for the period 2016 to 2020. This study uses the PLS-SEM analysis method with a quantitative approach. The results of this study indicate that the welfare of farmers has a significant influence on the financing of the agricultural sector. Meanwhile, financing risk does not have a significant effect on financing the agricultural sector.